Socioeconomic profile of students who have a grade point average "gpa"of 8.0, or above, from the fourth and fifth years of the bachelor in english With emphasis in teaching at the Department of Foreign Languages of the University of El Salvador in the year 2015. - Bonilla, Claudia Marisol
Knowing about the socioeconomic profile of students is a matter of such importance everywhere. Finding factors that influence students’ performance has become an interesting topic of study not only in our country but also in countries abroad. In Latin America, doing research on students’ academic performance has become a task of daily living for educational researchers. For example, there are research studies conducted primarily by OEI, UNESCO and UNICEF which have been carried out starting from the educational reform in 1990. These studies work as instruments to measure indicators of educational quality and living standards in the region. They show the development of people to enable the improvement of educational services quality and the modernization of role of the state. Three studies conducted at different universities in Mexico are included, in this historical framework, with the purpose of presenting information on socioeconomic factors that influence academic performance of students in Latin American countries. The first one is a study conducted at Instituto Tecnológico y de Estudios Superiores de Monterrey (ITEMS) Campus Toluca in 2002. In the study not only socioeconomic factors associated to academic performance of students were found but also verbal, mathematical, emotional and academic factors among others.